2021
DOI: 10.3310/hta25730
|View full text |Cite
|
Sign up to set email alerts
|

Improving continence in children and young people with neurodisability: a systematic review and survey

Abstract: Background Children and young people with neurodisability often need help to achieve socially acceptable bladder and bowel control. Approaches vary depending on whether or not the impairment results from spinal cord pathology that impairs motor control and sensation of the bladder and bowel. Currently, there is uncertainty about which interventions are effective. Objective The objective was to summarise the available evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 124 publications
(130 reference statements)
0
4
0
Order By: Relevance
“…Impairment of children and young people with spinal cord pathology however may mean achieving continence is not a realistic goal and therefore the use of continence products is necessary, which can be at a considerable cost if not provided through health services. 10 18 Recent research highlighted that provision of continence pads is inadequate and ad hoc, 19 20 perhaps due to the influence that commissioning and funding arrangements have on provision, as highlighted in the HP survey. Research has also shown that children in low-income families are four times more likely to be urinary incontinent than children in high-income families, 21 so those families who cannot afford continence products more likely experience compromised comfort and dignity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Impairment of children and young people with spinal cord pathology however may mean achieving continence is not a realistic goal and therefore the use of continence products is necessary, which can be at a considerable cost if not provided through health services. 10 18 Recent research highlighted that provision of continence pads is inadequate and ad hoc, 19 20 perhaps due to the influence that commissioning and funding arrangements have on provision, as highlighted in the HP survey. Research has also shown that children in low-income families are four times more likely to be urinary incontinent than children in high-income families, 21 so those families who cannot afford continence products more likely experience compromised comfort and dignity.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of incontinence on quality of life has previously been highlighted 24 29 and our findings reinforce the need for further research around availability and acceptability of toileting interventions to adequately support children and young people with neurodisability. Effectiveness of interventions is likely to impact opinions of acceptability; while the surveys gathered some information on perceived effectiveness, 10 further evidence would add to the knowledge around appropriate incontinence support for children and young people with neurodisability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations